Transforming gene from human stomach cancers and a noncancerous portion of stomach mucosa. - Sakamoto, H (1986)
DNAs from 21 human stomach cancers, 16 metastatic stomach cancers to lymph nodes, and 21 apparently noncancerous specimens of stomach mucosae from a total of 26 patients with stomach cancer were tested for their ability to induce neoplastic transformation of NIH 3T3 cells on transfection by the calcium phosphate precipitation technique. Three samples of DNA were shown to have transforming activity; one was from a primary stomach cancer of one patient, the second was from a noncancerous portion of stomach mucosa of the same patient, and the third was from a lymph node metastasis of stomach cancer from another patient. These transformants were tumorigenic in nude mice, and DNAs from the cells could induce secondary transformants. A portion of the transforming gene from the stomach cancer of one patient, which contained the sequences expressed in the NIH 3T3 transformants, was cloned. The transforming gene did not have any homology with the transforming sequences reported previously. We have applied the term hst to this novel human transforming gene. The transforming gene, hst, was found to be present in all the primary and secondary transformants induced by the other two samples of DNA.